Analysis And Design Of Cash Sales Accounting Information System at Alfamart Kembang Beji - Susanti Usman; Ratih Widyanti Putri (Publikasi Indonesia, 2025)
The rapid economy in the era of globalization opens up opportunities for new businesses, but also increases competition between companies. The company must carry out its operational activities effectively and efficiently. The implementation of an appropriate accounting information system and the latest technology is essential to improve competitiveness and operational efficiency. This study aims to analyze the ongoing cash sales accounting information system and its conformity with the internal control system, and design an alternative cash sales accounting information system. This research method uses qualitative data, the source of data in this study is carried out through literature studies, interviews, and direct observation. The analysis tools used are flowcharts, data flow charts (DFD), ERD, and normalization. The conclusion obtained from this study is that the cash sales accounting information system at Alfamart Kembang Beji has been well computerized, but there are still weaknesses in terms of separation of duties, document authorization, and incomplete documents. The finance department makes a turnover report that should be done by the accounting department. The researcher proposes improvements through flowchart creation, DFD, ERD, database design, and various document input-output designs to improve the existing system.